Prevalence of MMP-1 rs1799750 Polymorphism in Androgenetic Alopecia: A Cross-Sectional Study in an Indonesia Population - Andianto, Ivan Christian; Sajiwo, Damar; Sidarta, Erick (Molecular and Cellular Biomedical Sciences, 2025)
Background: Matrix metalloproteinase-1 (MMP-1) is an enzyme responsible for degrading extracellular matrix (ECM) components, particularly collagen. Overexpression of MMP-1 can accelerate ECM degradation, contributing to various pathological conditions. The most studied polymorphism in the promoter region of the MMP-1 gene is rs1799750, which has been linked to several diseases in previous studies. Androgenetic alopecia (AGA) is a condition characterized by the progressive miniaturization of hair follicles, influenced by androgen signaling and ECM remodeling. This study aimed to investigate the prevalence of MMP-1 gene polymorphism and its potential association with AGA.Materials and methods: This study included 50 subjects diagnosed with AGA and 50 subjects without AGA. All subjects completed a questionnaire that included gender, age, BMI, and ethnicity. DNA was extracted from blood samples for genotyping of the MMP-1 rs1799750 gene. Genotyping was performed using the PCR-RFLP method with AluI as the restriction enzyme. For validation, several samples were sequenced at Apical Scientific Laboratory, Malaysia.Results: Among the 50 subjects with AGA, 9 had the 1G/1G genotype, 26 had the 1G/2G genotype, and 15 had the 2G/2G genotype. Similarly, among the 50 subjects without AGA, 8 had the 1G/1G genotype, 27 had the 1G/2G genotype, and 15 had the 2G/2G genotype. The allele frequencies of 1G and 2G in the AGA group were 0.44 and 0.56, respectively, while in the non-AGA group, they were 0.43 and 0.57, respectively. Chi-square analysis of AGA and MMP-1 genotype yielded a p-value of 0.96, indicating no significant association between AGA and the MMP-1 genotype.Conclusion: In this study, the association between the MMP-1 gene polymorphisms rs1799750 with AGA was not observed.Keywords: Androgenetic Alopecia, matrix metalloproteinase-1, polymorphisms, rs1799750